2015
DOI: 10.3727/096368915x687020
|View full text |Cite
|
Sign up to set email alerts
|

Cold Preservation of Human Adult Hepatocytes for Liver Cell Therapy

Abstract: Hepatocyte transplantation is a promising alternative therapy for the treatment of hepatic failure, hepatocellular deficiency, and genetic metabolic disorders. Hypothermic preservation of isolated human hepatocytes is potentially a simple and convenient strategy to provide on-demand hepatocytes in sufficient quantity and of the quality required for biotherapy. In this study, first we assessed how cold storage in three clinically safe preservative solutions (UW, HTS-FRS, and IGL-1) affects the viability and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
(96 reference statements)
2
12
0
Order By: Relevance
“…Due to its cost-effectiveness and simplicity, cold storage with conventional hypothermia remains the main method for liver conservation. In fact, major advances in the field of organ preservation have included the development of new improved preservation solutions capable of reducing cold-induced cellular damage[ 46 ]. Euro-Collins solution was first developed in the 1970s; while more recently, University of Wisconsin (UW)[ 47 ] Celsior[ 48 ], Histidine-Ketoglutarate (HTK)[ 49 ] and Institute Georges Lopez (IGL-1)[ 50 ] solutions tend to be extensively used for liver transplantation.…”
Section: Static Cold Storage Machine Perfusion and Storage Solutionsmentioning
confidence: 99%
“…Due to its cost-effectiveness and simplicity, cold storage with conventional hypothermia remains the main method for liver conservation. In fact, major advances in the field of organ preservation have included the development of new improved preservation solutions capable of reducing cold-induced cellular damage[ 46 ]. Euro-Collins solution was first developed in the 1970s; while more recently, University of Wisconsin (UW)[ 47 ] Celsior[ 48 ], Histidine-Ketoglutarate (HTK)[ 49 ] and Institute Georges Lopez (IGL-1)[ 50 ] solutions tend to be extensively used for liver transplantation.…”
Section: Static Cold Storage Machine Perfusion and Storage Solutionsmentioning
confidence: 99%
“…A variety of preservation solutions, such as ViaSpan (University of Wisconsin solution), Celsior, Custodiol histidine‐tryptophan‐ketoglutarate solution and, more recently, HypoThermosol (HTS), were developed taking these factors into consideration [15] and are commercially available today. These solutions showed to be effective for hypothermic storage of a large diversity of cells, tissues, and organs (including neonatal rat ventricular cardiomyocytes [16], renal cells [17], hepatocytes [18, 19], liver tissue [20], synthetic human epidermis tissue [21], kidney [22], pancreas [23], liver [20], and heart [24, 25]). Importantly, some of these formulations can be directly administered into patients, avoiding additional poststorage culture manipulations/costs and washing steps.…”
Section: Introductionmentioning
confidence: 99%
“…As a potential simple and convenient strategy, hypothermic preserved human hepatocytes offer the opportunity to repeat studies at different times using cells from the same single donor or a combination of multiple donors [30]. Although cold storage has a deleterious effect on the viability of human hepatocytes, studies have shown that the albumin secretion, coagulation factor VII, Phase II activities and ammonia metabolism of the remaining viable cells are comparable to fresh hepatocytes [37,38]. Besides, in cryopreserved hepatocytes, the activities of most drug-metabolizing enzymes, glutathione transferase and various transporters are similar to those in freshly isolated cells [35,36].…”
Section: Hypothermic Storage Of Isolated Human Hepatocytesmentioning
confidence: 99%